Heat transfer augmentation through rectangular cross section duct with one corrugated surface: An experimental and numerical study - Shimaa Zahran; Ahmed A. Sultan; Maher Bekheit; Mohamed R. Elmarghany (Case Studies in Thermal Engineering, 2022)
One of the techniques utilized to enhance the heat transfer rate within air ducts is creating turbulence inducing designs. In this work, turbulent air flow through a rectangular cross-sectional duct with one corrugated surface was experimentally and numerically investigated. Hydraulic and thermal behaviors of the system were evaluated at different Reynolds numbers. A test rig was constructed to experimentally investigate the performance. Also, a two-dimensional computational fluid dynamics simulation was performed using k-ε model to simulate fluid flow within the duct. The model was validated against previous results as well as the experimental results from this research. The computational and experimental findings were in reasonable agreement with a maximum error of less than 10%. The results showed that the existence of the corrugated surface considerably enhanced the heat transfer rate in all the studied cases, while slightly increasing the pressure drop. Consequently, a parametric study was performed to investigate the effect of different design parameters on the performance. The best performance was observed at a rib height to width ratio of 0.2, and groove length to width ratio of three, with a thermal enhancement factor of about 1.5. an empirical relation between Nusselt number and Reynolds number was established using the obtained results with a relative error value less than 8%. The study proved the value of using a corrugated surface as a means to increase heat transfer rate within rectangular air ducts.